Analisis Kinerja Keuangan PT Total Bangun Persada Tbk: Pendekatan Profitabilitas, Likuiditas, dan Solvabilitas: Analysis of Financial Performance of PT Total Bangun Persada Tbk: Profitability, Liquidity, and Solvency Approach - Ikfal Permana; Alfiansyah Wahyu Pratama; Muhammad Davi Rivaldi; Alif Shafiar (PT Cakrawarti Empat Proksi, 2026)
This study aims to analyze the financial performance of PT Total Bangun Persada Tbk (TOTL) during the 2022-2024 period through an analysis approach of trends, Common Size, and financial ratios (profitability, liquidity, and solvency), as well as compare it with the average building construction industry in Indonesia. The data used is secondary data in the form of annual financial statements published through the Indonesia Stock Exchange (IDX). The results show that TOTL has better profitability than the industry average, with a net profit Margin that increased from 4.03% (2022) to 8.60% (2024). However, the company's liquidity and solvency aspects were recorded relatively lower than the industry average, driven by the dominance of current debt in the funding structure. The 2025 projection shows moderate profit growth, supported by new contracts worth IDR 2.49 trillion in the first semester of 2025. This research recommends management to optimize capital structure and maintain liquidity ratios to remain competitive amid industry pressures. The results of this study imply that companies need to maintain profitability advantages through operational efficiency while improving their capital structure so that short-term liquidity risks can be minimized.